Pengaruh Pemberian Kompos Bagase terhadap Serapan Hara dan Pertumbuhan Tanaman Tebu (Saccharum officinarum L.) - Dwi Guntoro; , Purwono; , Sarwono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The effect of bagase compost application on nutrient uptake and growth of sugarcane was studied at PG Jatitujuh. Majalengka, West Java, from October 1998 to March 1999. The experiment was arranged in split plot design with three replications. The bagase compost as sub plot and the recommended rate of inorganic fertilizer as the main plot. The rates of bagase compost were 0.0, 2.5, 5.0, and 7.5 ton/ha and the recommended rate of inorganic fertilizers were 100%, 75%, and 50% of recommended rate. The recommended rate of inorganic fertilizer was 300 kg Urea, 200 kg ZA, 150 kg SP-36, and 200 kg KCl/ha. The results showed that bagase compost application at 7.5 ton/ha significantly increased nitrogen uptake at 3 Month After Planting (MAP) compared to no compost, but did not affect P2O5, K2O and  S. Lower rate of inorganic fertilizer decreased S uptake at 2 MAA, but did not affect N, P2O5 dan K2O. Combination of 5.0 ton/ha compost bagase with 100% recommended rate of inorganic fertilizer tended to increase sugarcane growth. Bagase compost application with inorganic fertilizer did not affect the percentage of growth, height, and diameter off  stalk.   Key words: Sugarcane, Bagase compost, Nutrient uptake